2004
DOI: 10.3354/dao059101
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of spotted wolffish Anarhichas minor to experimental infection with nodavirus and infectious pancreatic necrosis virus

Abstract: The spotted wolffish Anarhichas minor is a promising new species for cold-water aquaculture. The broad host-range of piscine nodavirus (NV) and infectious pancreatic necrosis virus (IPNV) makes them potentially pathogenic to new fish species in aquaculture. IPNV and NV strains highly pathogenic in farmed Atlantic salmon Salmo salar and halibut Hippoglossus hippoglassus, respectively, in Norway were used for the challenge of spotted wolffish. In general, water-borne infection with IPNV and NV resulted in signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…In Atlantic halibut Hippoglossus hippoglossus of 20 g, no clinical signs of mortality were observed, but Q-PCR detection revealed an increase in virus in brain tissue post injection (Grove et al 2003). In similar studies in spotted wolffish Anarhichas minor, a nodavirus originating from Atlantic halibut caused mortality in 10 g fish after intraperitoneal and intramuscular injections as well as in 0.7 g juveniles after bath-challenge , Sommer et al 2004). However, reports on juvenile sea bream Sparus aurata suggest that there are differences in host susceptibility, as intraperitoneal injection failed to reproduce clinical signs (Aranguren et al 2002).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In Atlantic halibut Hippoglossus hippoglossus of 20 g, no clinical signs of mortality were observed, but Q-PCR detection revealed an increase in virus in brain tissue post injection (Grove et al 2003). In similar studies in spotted wolffish Anarhichas minor, a nodavirus originating from Atlantic halibut caused mortality in 10 g fish after intraperitoneal and intramuscular injections as well as in 0.7 g juveniles after bath-challenge , Sommer et al 2004). However, reports on juvenile sea bream Sparus aurata suggest that there are differences in host susceptibility, as intraperitoneal injection failed to reproduce clinical signs (Aranguren et al 2002).…”
Section: Discussionmentioning
confidence: 76%
“…Resale or republication not permitted without written consent of the publisher Dis Aquat Org 68: 7-15, 2005 such as cod Gadus morhua (Starkey et al 2001, Johnson et al 2002, Gagne et al 2004, Atlantic halibut Hippoglossus hippoglossus (Grotmol et al 1995, Grotmol et al 1997b) and spotted wolffish Anarhichas minor , Sommer et al 2004. In Norway, Atlantic halibut hatcheries have suffered several outbreaks of VER during the past few years (Dannevig et al 2000, Johansen et al 2004a, suggesting the persistence of virus in cultured populations.…”
Section: Abstract: Nodavirus · Atlantic Salmon · Atlantic Halibut · mentioning
confidence: 99%
“…When this IPNV strain was used for challenge of smaller juveniles of spotted wolffish, titres of 10 5 to 10 8 TCID 50 g -1 tissue were registered in IPN-diseased fish after 4 wk. The infection was reported to still persist after 4 mo with titres of 10 3.5 TCID 50 g -1 tissue, demonstrating a carrier state of IPNV (Sommer et al 2004). Whether the present experimental IPNV infection in cod would have developed into a carrier state is not known.…”
Section: Discussionmentioning
confidence: 83%
“…Error bars: SEM (n = 10). *Significant differences to the calibrator (p < 0.05) generally the most susceptible to IPNV-induced mortality (Novoa et al 1993, Biering et al 1994, Sommer et al 2004), but the viral strain and water temperature also have an influence (Saint-Jean et al 2003, Santi et al 2004. The viral strain used in this experiment was originally isolated from IPN diseased halibut fry and has caused high mortality in bath-challenged spotted wolffish fry (Sommer et al 2004).…”
Section: Discussionmentioning
confidence: 95%
“…In Norway, this virus has been detected in several fish species including farmed ones such as turbot Scophthalmus maximus (Bloch et al 1991, Johansen et al 2004, Atlantic halibut Hippoglossus hippoglossus (Grotmol et al 1995, Aspehaug et al 1999, Hellberg & Dannevig 2002, 2003 and Atlantic cod Gadus morhua (Patel et al 2007). In addition, spotted wolfish Anarhichas minor (Johansen et al 2003, Sommer et al 2004 and Atlantic salmon Salmo salar (Korsnes et al 2005) were found to be susceptible by intraperitoneal (i.p.) injection with NNV.…”
Section: Introductionmentioning
confidence: 99%